Big data, analytics and artificial intelligence for sustainability - Bolanle A. Ojokoh; Oluwarotimi W. Samuel; Olatunji M. Omisore; Oluwafemi A. Sarumi; Peter A. Idowu; Emile R. Chimusa; Ashraf Darwish; Adebayo F. Adekoya; Ferdinand A. Katsriku (Scientific African, 2020)
Big data technologies, Analytics and Artificial Intelligence are great tools with capabilities to accomplish complex tasks at levels beyond human skills. The trio are becoming more and more prominent these days as they can be utilized to collect, organize, and analyze large varied data sets in order to reveal hidden patterns and trends that can help address several problems peculiar to sustainable development. Nevertheless, a number of challenges arise in the process of exploring these technologies for proffering solutions. This special issue presents novel research approaches adopted in Africa in relation to Big Data, Analytics and Artificial Intelligence in different domains. It also presents the challenges and issues that can be explored in the future.